Impact of COVID-19 pandemic and infection on in hospital survival for patients presenting with acute coronary syndromes: A multicenter registry. (1st June 2021) - D'Ascenzo, Fabrizio; De Filippo, Ovidio; Borin, Andrea; Barbieri, Lucia; Adamo, Marianna; Morici, Nuccia; Truffa Giachet, Alessandra; Iannaccone, Mario; Crimi, Gabriele; Gaido, Luca; Bocchino, Pier Paolo; Pivato, Carlo Andrea; et al.
Abstract: Introduction: The impact of Covid-19 on the survival of patients presenting with acute coronary syndrome (ACS) remains to be defined. Methods: Consecutive patients presenting with ACS at 18 Centers in Northern-Italy during the Covid-19 outbreak were included. In-hospital all-cause death was the primary outcome. In-hospital cardiovascular death along with mechanical and electrical complications were the secondary ones. A case period (February 20, 2020-May 3, 2020) was compared vs. same-year (January 1–February 19, 2020) and previous-year control periods (February 20–May 3, 2019). ACS patients with Covid-19 were further compared with those without. Results: Among 779 ACS patients admitted during the case period, 67 (8.6%) tested positive for Covid-19. In-hospital all-cause mortality was significantly higher during the case period compared to the control periods (6.4% vs. 3.5% vs. 4.4% respectively; p 0.026), but similar after excluding patients with COVID-19 (4.5% vs. 3.5% vs. 4.4%; p 0.73). Cardiovascular mortality was similar between the study groups. After multivariable adjustment, admission for ACS during the COVID-19 outbreak had no impact on in-hospital mortality. In the case period, patients with concomitant ACS and Covid-19 experienced significantly higher in-hospital mortality (25% vs. 5%, p < 0.001) compared to patients without. Moreover, higher rates of cardiovascular death, cardiogenic shock and sustained ventricular tachycardia were found in Covid-19 patients. Conclusion: ACS patients presenting during the Covid-19 pandemic experienced increased all-cause mortality, driven by Covid-19 positive status due to higher rates of cardiogenic shock and sustained ventricular tachycardia. No differences in cardiovascular mortality compared to non-pandemic scenarios were reported. Graphical abstract: Impact of Covid-19 pandemic and infection on the risk of all-cause death, cardiovascular mortality and acute myocardial infarction-related mechanical and arrhythmic complications among patients presenting with acute coronary syndrome. Legend: ACS: acute coronary syndrome; CV mortality: cardiovascular mortality; MCS: mechanical circulatory support; STEMI: ST-segment elevation myocardial infarction; MINOCA: myocardial infarction with non-obstructive coronary artery disease. Unlabelled Image Highlights: Conflicting results about cardiovascular outcomes of patients admitted for ACS during COVID-19 pandemic exists. We found a higher rate of death among patients admitted for ACS in the pandemic context as compared to control periods. Such difference was driven by patients suffering from both ACS and Covid-19 infection. Patients suffering from both ACS and Covid-19 experienced higher rates of acute in-hospital AMI-related complications. Covid-19 was associated with higher rates of malignant ventricular arrythmias, cardiogenic and septic shock.